Feeding of Aspergillus oryzae fermentation culture (AOFC) to growing sheep: 2. Growth rate and feed efficiency - D Lubis; B Haryanto; E Wina; T Suhargiyantatmo (Indonesian Center for Animal Research and Development (ICARD), 2002)
Utilization of yeast and or filamentous fungi as feed additive to ruminants has been of interest since the late 1980’s. Two fungi species have been commercially produced in the United States, (1) Yea-Sacc containing living cells of Saccharomyces cerevisiae and (2) Amaferm bearing Aspergillus oryzae fermentation extract. It has been demonstrated and proven that the cultures can enhance rumen development and function in young ruminants. This paper concerns the use of Aspergillus oryzae fermentation culture (AOFC) as feed additive for young-growing male ‘Garut’ sheep. The A. oryzae was cultured in a media made of mineral-enriched ‘onggok’ flour, a material of tapioca processing waste. The AOFC was prepared gradually by incubating the fungus at room temperature (26 – 300C) for 5 days, dried at 400C and ground. The AOFC was added to a commercial concentrate (GT-03) at 0, 5 and 10% (w/w) levels, as treatment C0 (control), C1, and C2, respectively. Fifteen growing ‘Garut’ sheep were used and the concentrate feed treatments were randomly allotted based on a randomized block design. Drinking water was available at all time. The amount of feed offered (chopped King grass and concentrates) and their refusals were weighed daily and live-weight of sheep was measured once a week in the morning. Daily feces was collected and weighed in the last 10 days of the 14-week experimental period. All feed and fecal samples were analyzed for dry matter, crude protein, total fiber (NDF), and ash. AOFC supplementation resulted in higher weight gains (P<0.05), which were 94.81; 122.08; and 140.52 g/d for C0, C1, and C2 treatments, respectively. Dry and organic matter, as well as protein intake was also significantly increased by inclusion of AOFC into concentrate diet (P<0.05). The increment in nutrient intake was from increased consumption of concentrates, and not from King grass, however, there was no effect of AOFC supplementation on feed efficiency. Key words: A. oryzae, sheep, gain, efficiency